Proceedings of the 31st International Technical Meeting of the Satellite Division of the Institute of Navigation (ION GNSS+ 201 2018
DOI: 10.33012/2018.15931
|View full text |Cite
|
Sign up to set email alerts
|

FLAMINGO - Fulfilling Enhanced Location Accuracy in the Mass-market through Initial Galileo Services

Abstract: This paper discusses FLAMINGO, an initiative that will provide a high accuracy positioning service to be used by mass market applications. The status and future for the initiative are discussed, the required accuracies and other location parameters are described, and the target applications are identified. Finally, the currently achieved accuracies from today's Smartphones are assessed and presented. FLAMINGO (Fulfilling enhanced Location Accuracy in the Mass-market through Initial GalileO services), part fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…The NSL's FLAMINGO (Nottingham Scientific Limited's fulfilling enhanced location accuracy in the massmarket through Initial Galileo Services) team investigated the PPP and RTK performance of the dual-frequency Xiaomi Mi8 smartphone (Fortunato et al, 2019a;Roberts et al, 2018). The results confirmed that the carrier-phase observations from the Xiaomi Mi8 were not affected by the duty cycling and employing the L5/E5a observations could improve the positioning accuracy (Fortunato et al, 2019a;Roberts et al, 2018). Robustelli et al (2019) assessed the performance of a Xiaomi Mi8 smartphone in terms of the pseudorange multipath and noise compared with a geodetic receiver using the multipath linear combination.…”
Section: Absolute Positioningmentioning
confidence: 99%
“…The NSL's FLAMINGO (Nottingham Scientific Limited's fulfilling enhanced location accuracy in the massmarket through Initial Galileo Services) team investigated the PPP and RTK performance of the dual-frequency Xiaomi Mi8 smartphone (Fortunato et al, 2019a;Roberts et al, 2018). The results confirmed that the carrier-phase observations from the Xiaomi Mi8 were not affected by the duty cycling and employing the L5/E5a observations could improve the positioning accuracy (Fortunato et al, 2019a;Roberts et al, 2018). Robustelli et al (2019) assessed the performance of a Xiaomi Mi8 smartphone in terms of the pseudorange multipath and noise compared with a geodetic receiver using the multipath linear combination.…”
Section: Absolute Positioningmentioning
confidence: 99%
“…Since then, researchers have embarked on comprehensive investigations into the positioning performance of dual-frequency GNSS smartphones. In studies [16,17], it was revealed that incorporating L5/E5a measurements can significantly enhance positioning accuracy. Robustelli et al [18] conducted an assessment of code measurements, considering pseudo-range noise and multi-path errors.…”
Section: Introductionmentioning
confidence: 99%